New Perspectives about Maxillary Sinus Lifting: a Literature Review - Barros, Mariana Silva; Amaral, Regiane Cristina do; Pedron, Irineu Gregnanin; Shinohara, Elio Hitoshi; Gaujac, Cristiano (ARCHIVES OF HEALTH INVESTIGATION, 2023)
Maxillary sinus lifting is a procedure for bone height gain in atrophic jaws. New safe and less complex manners have been evalueted, which use modifications of conventional techniques, through technologies such as devices and equipment that make them less traumatic. This study aims to conduct a literature review of articles found in the PubMed database between the years 2015 and 2020 that addresses advances in Maxillary sinus lifting techniques. We noticed that there is a development in the techniques that promotes the reduction of operative time, perforations and consequently a better postoperative for the patient, reducing the unpleasant perception of the surgery. The use of surgical ultrasound reduces the trauma to the soft tissues and the number of membrane perforations. A great step in the development of the sinus membrane lifting technique was the perception that bone formation is possible with the detachment of the membrane, not requiring the placement of a graft. There is no technique that replaces Maxillary Sinus Lifting yet. Only to improve it.